Anterior cruciate ligament rehabilitation and return to sport in rock climbing athletes: a practical concept paper - Vagy, Jared; Schöffl, Volker; Ohde, Julia; Petersen, Wolf; Lutter, Christoph (Frontiers in Sports and Active Living, 2025)
BackgroundAcute ACL tears are becoming increasingly common among rock climbing athletes, particularly those who engage in bouldering.Hypothesis/purposeThe purpose of the paper was to develop a rehabilitation and return to sport protocol for rock climbing athletes after an anterior cruciate ligament reconstruction.Study designThe protocol is designed in 6 phases and emphasizes the importance of sport-specific postoperative rehabilitation protocols that address the unique needs of rock climbing athletes and stresses the need for sport-specific training prior to returning to full activity.MethodsThe proposed rehabilitation protocol follows the stages of typical postoperative ACL protocols but with an emphasis on climbing-specific demands, such as eccentric landing mechanics and penduluming into a wall during lead climbing.ResultsClimbers will be able to utilize the protocol to return to rock climbing.ConclusionThis paper highlights the need for further research on the topic and provides a foundation for future studies examining ACL tears in climbing athletes.